Book Review - Patankar, P. R. (Journal of Engineering Education Transformations, 1994)
Although quality is perplexing to define and difficult to measure, the pursuit of quality is not new in the industrial field. Starting from inspection and quality control with the advent of mass production, it has passed through various stages such as statistical quality control, quality assurance etc.